(untitled) (Journal of Hama University, 2025)
Chronic kidney failure and the process of hemodialysis are among the major health challenges faced by individuals worldwide. Therefore, self-care behaviors play a crucial role in the lives of patients as they contribute to improving treatment outcomes and the quality of life. This study aimed to explore self-care behaviors among hemodialysis patients. The sample consisted of 40 male and female patients, and data were collected at Tishreen University Hospital in Latakia. The results indicated that more than half of the patients had moderately implemented self-care behaviors, while more than quarter of the patients had highly implemented behaviors. Regarding self-care behaviors specific to the disease, the results showed that the majority of patients implemented these behaviors at a minimum level. The study recommended to develop a comprehensive educational program for self-care among patients, which could assist them in managing their daily lives and dealing with potential problems.